INTER RATER RELIABILITY AS QUALITY ASSURANCE OF KFZA TRANSLATION INTO INDONESIAN LANGUAGE - Ratri Atmoko Benedictus (MANASA, 2017)
Translation of a psychological measuring instrument is one of the harmonization efforts towards a cultural context, especially in terms of language. The process is not just utilizing the sophistication of translator technology, but also need to do an evaluation of the accuracy of a translation. This article aims to measure the degree of quality of early translation accuracy of a psychological measuring instrument, i.e. KFZA that measures work stress. KFZA itself stands for Kurz-Fragebogen zur Arbeitsanalyse that is developed by Prumper, Hartmannsgruber and Frese in the German language. The result indicated that the coefficient of Cohen’s kappa (k) is .458 and it represents a weak of agreement between the two raters, although it is reliable at the 0.05 level. Since initial translation is a critical step of psychological test translation and adaptation, competence qualifications of each rater and the equivalence of competencies between raters are very important.